Pelaksanaan Kurikulum Merdeka Belajar dalam Meningkatkan Proses Pembelajaran di SMPN 1 Karawang Barat - Anjani, Putri; Permana, Hinggil; Husein, Ceceng Syarif (Jurnal Ilmiah Wahana Pendidikan, 2025)
The curriculum is one of the important aspects that support the success of an educational institution, especially in Indonesia. Therefore, the independent learning curriculum has become the goal of the Ministry of Education, Culture, Research, and Technology to create a better learning process than the previous curriculum. The independent learning curriculum is the latest breakthrough where students are the main focus in developing their potential and character through P5 (Projek Penguatan Profil Pelajar Pancasila or the Project for Strengthening the Pancasila Student Profile). In examining the title of this research, the researcher employed a qualitative research method based on findings observed through phenomena occurring in the implementation of the independent learning curriculum to enhance the learning process at SMPN 1 Karawang Barat. It can be concluded that the implementation of the independent learning curriculum at SMPN 1 Karawang Barat includes procedures and strategies that can be used as a basis for linking the learning process with the development of students' potential and character. Additionally, the implementation by SMPN 1 Karawang Barat serves as a benchmark for preparing teachers to conduct an effective and efficient learning process, tailored to the understanding and characteristics of each student. However, there are obstacles in the procedures and strategies, such as possible mismatches between the planned learning and the teaching modules prepared.